2018
DOI: 10.20945/2359-3997000000043
|View full text |Cite
|
Sign up to set email alerts
|

Maternal hypothyroxinemia in the first trimester of gestation and association with obstetric and neonatal outcomes and iron deficiency: a prospective Brazilian study

Abstract: This prospective Brazilian study found no association between isolated hypothyroxinemia in the first trimester of gestation and obstetric or neonatal outcomes, but an association was demonstrated with iron deficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…The articles were published in various geographical region: North America (15) and USA (14,20)], South America [Brazil (16)], Europe [Netherland (21,24,29), Spain (22), Finland (23) and Ireland (28)] and Asia / Australia [China (6,11,26,27) and Australia (25)]. All studies were prospective or retrospective cohorts and 47% (7/15) had a population-based design (21-23, 26, 27, 29, 30).…”
Section: Search Results Study Selection and Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…The articles were published in various geographical region: North America (15) and USA (14,20)], South America [Brazil (16)], Europe [Netherland (21,24,29), Spain (22), Finland (23) and Ireland (28)] and Asia / Australia [China (6,11,26,27) and Australia (25)]. All studies were prospective or retrospective cohorts and 47% (7/15) had a population-based design (21-23, 26, 27, 29, 30).…”
Section: Search Results Study Selection and Characteristicsmentioning
confidence: 99%
“…However, IMH was not associated with other neonatal outcomes including NICU admission (14,16), low Apgar score (14,15), umbilical artery blood pH < 7 (14), RDS (14), necrotizing enterocolitis (14,16), intraventricular haemorrhage (14,16), major malformations (14,16,25,26), perinatal mortality and neonatal death (14,16,20,25,26), or neurodevelopmental disturbances (26).…”
Section: Neonatal Outcomesmentioning
confidence: 94%
See 1 more Smart Citation
“…Two studies reported an association between isolated hypothyroxinemia and iron deficiency anemia; however, they found no associations with negative obstetrical or neonatal outcomes (31,32). In a prospective study of 660 pregnant, Brazilian, TPOAb negative women, Rosario et al found that women with iron deficiency had higher rates of isolated hypothyroxinemia of either free thyroxine (fT4) <0.92 ng/dL, <0.86 ng/dL or TT4<7.8 ng/dL, at 20.7, 14.8, and 17.2%, respectively, compared to women without iron deficiency at 8.4, 3.9, and 6.5%, respectively, P = 0.038, 0.032, and 0.045, respectively, but found no associations between isolated hypothyroxinemia with other obstetrical or neonatal outcomes (32). In a prospective study of 292 pregnant, Georgian women with isolated hypothyroxinemia compared to 58 controls, Morchiladze et al (27) (31).…”
Section: C) Treatment Of Subclinical Hypothyroidism (Question 37)mentioning
confidence: 99%
“…Little was published on the relationship between isolated hypothyroxinemia and adverse pregnancy outcomes when the 2017 ATA Guidelines were published, and this remains true today. Two studies have reported an association between iron deficiency anemia and isolated hypothyroxinemia (31,32), however, there were a large number of tested variables, without correction for the multiple comparisons. Both studies are thus vulnerable to a high risk of false positive findings; therefore, further studies are needed.…”
Section: C) Treatment Of Subclinical Hypothyroidism (Question 37)mentioning
confidence: 99%